ANALISIS STRATEGI SOAR DALAM MENINGKATAKAN PEMASARAN KALIBRASI DI PT. PAL INDONESIA - Imam Ramadhani; Rusindiyanto (JOURNAL SAINS STUDENT RESEARCH, 2024)
PAL Indonesia, as a leading company in the production of the main defense system equipment in Indonesia, especially in the marine sector, is the largest producer in this country. This company consists of 22 divisions, including the Technology & Quality Assurance Division. This division is divided into several departments, one of which is the ISO, Standardization & Calibration Department. Within the department, there were fluctuations in calibration marketing strategies. Therefore, SOAR analyzes existing marketing strategies in calibration. In this research, the SOAR method as an analysis of the marketing strategy implemented by PT PAL Indonesia is appropriate by comparing the previous strategy. The study results show that to achieve certain marketing strategies in managing service quality. The goal is to provide service to customers in accordance with better service work standards to meet customer expectations and industry standards at PT. PAL Indonesia.